Strategic Allinaces in Financial Institutions: An Exploratory Study in the Malaysian Context - Adenrele, Omolara O. (2007)
With an increasingly competitive business environment, and more discerning customers with a myriad of needs, organisations are faced with several strategic decisions in pursuit of growth. Increased pressures from globalization which has created a no boundary global economy drives organisations to seek out the optimum growth strategies that will not only leverage on the emerging opportunities but also create sustainable competitive advantage. It thus becomes imperative for business to adopt the right strategy to address the challenges. Strategic Alliances is one of the many options open to businesses, and that is the concept being explored in this study.The objective of this study is to explore strategic alliance as a concept with a focus on how it is being exploited in the Malaysian financial industry, specifically in the banking sector to create competitive advantage. With a highly regulated financial industry in Malaysia, it will be interesting to see how both domestic and foreign banks leverage on the use of partnerships to overcome challenges and create competitive advantage. This study seeks to examine the main motives for which banks are forming strategic alliances and how critical these partnerships are for operating within Malaysia given the degree of regulation in the industry. Also to identify the forces driving the motivation to form Strategic Alliances and what types of alliances are being formed. This research conducts four bank case studies to understand the motives and alliance preference of the banks. The case studies are ground up and built on data gathered from secondary sources and from structured interviews with bank managers. This research entails the evaluation of alliance purpose and types of two foreign banks and two local banks, this allows for comparison to be made between the two different categories of banks based on their motives and type.The findings of this research show a major commonality in the motives of both the local and foreign banks for forming alliances. It was also observed that the foreign banks are more motivated to form alliances for the purpose of increasing their sales and distribution channels,possibly because their activities are highly regulated by government. The major force driving the motivation of banks to form alliances is the increasing pressures of having to satisfy the countless array of customers needs. Consequently all banks want to become a universal financial services provider. Evident from the study of the four banks, equity alliances are more prominent forms of collaborations between financial institutions that offer complementary services, in the bid to expand their product offerings. All four banks engage in some form of equity alliance, where the foreign banks collaborate with local financial institutions and the local banks partner with foreign financial institutions in order to access new markets.Further research may examine the criterion for selecting a strategic alliance partner, which is a very critical aspect of forming alliances. Further investigation may also be done on the factors that influence the selection of types of alliances adopted by business such as organizational culture, government intervention or employees’ culture factors.